The customer-base audit : the first step on the journey to customer centricity - Fader, Peter S.; Hardie, Bruce G. S.; Ross, Michael (Data scientist) (Ascent Audio, 2023)
As a leader in your organization, you will be very familiar with your organization's key financial statements and monthly management reports. You may have spent countless hours discussing budgets and expenditures. But how much time have you spent reflecting on the fact that these revenues are generated by actual customers-the people who pull out their wallets and pay for your products and services? In The Customer-Base Audit: The First Step on the Journey to Customer Centricity, experts Peter Fader, Bruce Hardie, and Michael Ross start you on the path toward really getting to understand your customers' buying behavior as well as the health of your overall customer base. A customer-base audit is a systematic review of the buying behavior of a firm's customers using data captured by its transaction systems. It will help you answer questions such as: How healthy is your customer base? How realistic are your growth objectives?; How do your customers differ in terms of their behavior and value?; How has the quality of your customers changed over time?; What changes in customer behavior lie behind period-to-period changes in firm performance?; What is important to your high-value customers?; and Which products help you acquire and retain your best customers?